A novel on-time partial shading detection technique for electrical reconfiguration in solar PV system. (1st September 2021) - Sugumar, S.; Prince Winston, D.; Pravin, M.
Graphical abstract: Highlights: Partial shading is detected on-time without disconnection of load from PV array. Short circuit current measurement is not required in the proposed technique. Sensor requirement is less than the conventional technique hence cheaper. Quick detection of partial shading leads to more energy extraction. Mismatch loss is greatly reduced in the proposed technique. Abstract: Mismatch losses due to partial shading condition (PSC) is not permitted to extract maximum power from the solar PV array. Numerous techniques were proposed to reduce the partial shading effect. But the major problem is in finding out the occurrence and its distribution of the partial shading in the solar PV array. Conventional methods disconnect the load temporally from the PV array and measure the short circuit current ( I sc ) and use the information to detect the partial shading. Frequent disconnection of the solar PV array from the load makes the conventional method unpractical in a large solar power plant and even a stand-alone PV system. A novel on-time partial detection technique is proposed in this paper and useing difference in row voltage (Vd ) instead of the short circuit current ( I sc ) to estimate the partial shading. Greater the Vd infers the severity of occurrence of the partial shading in the solar PV array. By using a static reconfiguration and then a modified couple matching (MCM) technique the voltage difference (Vd ) gets reduced. This will ensure the mitigation of the PSC. As in this proposed technique, the load never be disconnected from the solar PV array, to detect the partial shading, it can be used practically even for a stand-alone PV system. Eight extensive partial shading patterns are simulated using MATLAB Simulink to validate the proposed work and the size of 3 × 4 120 W polycrystalline PV panel array is used for the experimental validation.